Ricardo Darín and the Construction of Latin American Film Stardom - Garavelli, Clara (International Film Stars : IFS, 2023)
Examines the star persona of Argentine actor Ricardo DarínOffers the first academic study that analyses the full spectrum of Darín's works - in theatre, film and TV, filling a lacuna both in Hispanic and Anglophone academiaSets out an innovative exploration of Darín's star construction and cultural significance in connection to the dynamics of the Argentine film industry and the Latin American and Hispanic star stereotypesExamines currently unanswered questions regarding Stardom in Latin AmericaReveals performative features of Darín's work that define Argentine cinema's contemporary mainstream productionsProvides accounts of Darín's influences in the national and international cinema marketplaceThis monograph examines the figure of Ricardo Darín, the leading actor that drives Argentine cinema's box office success. It aims to fill a lacuna both in Hispanic and Anglophone academia regarding the study of how Ricardo Darín's rise to stardom took place, and what that stardom means for the Latin American film industry. Accordingly, it examines whether or not Ricardo Darín embodies the epitome of the contemporary Latin American or Hispanic star, and, importantly, whether or not the characteristics of the Hollywood star system are actually applicable in the case of Argentine cinema - where the dividing lines between so-called 'industrial' and 'independent' cinemas are very difficult to discern. Thus, whilst taking the study of this key figure from contemporary Argentine cinema as its focal point, this study will also facilitate an opening up towards broader but equally vital questions that continue to require full examination: How are Argentine, Latin American and Hispanic stars constructed? Does the leading actor of contemporary Argentine cinema embody a wider social group and historical moment in the region? Is his performative approach redefining a particular cinematic style?